A Research on Inadequacies in Indian Education System - KUMAR, MR. MANISH (The journal of contemporary issues in business and government, 2021)
The education system was brought into existence for the very reason that education is intrinsic to the growth of an individual which eventually leads to the growth of society, state, country, continent and ultimately the world. Hence, education is the single most important element that is intrinsic to the growth and development of the society without a single doubt. It is important to dive deeper into the purpose, shortcomings, issues and areas needing improvement and this paper specifically deals with these areas. The primary purpose of education is to advise or mentor an individual to live his life in a useful and meaningful method. The diversity in the quality of education is be one of difficulty or complication in the education system is diversity in the quality of education. It is true that the character or excellence of education is a reflection of prosperity. Hence this research paper highlights the problems of the Indian education system, the main areas that have been highlighted are the need and importance of education and the primary challenges of this system, with suggestions for improving it.